Your creative brain seven steps to maximize imagination, productivity, and innovation in your life - Carson, Shelley 1949- (Jossey-Bass, 2010)
"Filled with research-based techniques for expanding creativity and increasing productivity This provocative book reveals why sitting in front of a light box can increase your creativity more than listening to a Bach concerto as example. The author Shelley H. Carson, a Harvard psychologist, explains that creativity isn't something only scientists, investors, artists, writers, and musicians enjoy, but rather all of us use our creative brains every day at home and at work and have the ability to increase our mental functioning and creativity by understanding the seven brainsets. Explains the seven brainsets of the mind and their functions as related to creativity, productivity, and innovation, including Open, Scan, Think, Vision, Appraise, Streaming and Goal Provides quizzes, exercises, and self-tests to activate each of these seven brainsets to unlock our maximum creativity This book is a Harvard Health Publication that offers helpful suggestions that can be applied in both your personal and professional life."-- |c Provided by publisher.